2020
DOI: 10.1016/j.gendis.2019.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel FZD6 mutation revealed the cause of cleft lip and/or palate in a Chinese family

Abstract: Cleft lip and/or palate (CL/P) is a most common craniofacial birth defect which has multifactorial etiology. In our study, we aimed to discover the underlying etiological gene variation in a Chinese family diagnosed as non-syndromic CL/P (NSCL/P). The blood sample of the proband and her parents were detected by whole exome sequencing. The Mendelian inheritance pattern, allele frequency, variation location, function analysis and literature search were applied to filtrate and screen the mutation. Besides, the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the etiology of NSCLP is heterogeneous and closely related to genetic and environmental factors [1,3,4,7]. However, a singlegene mutation may contribute more significance in a hereditary NSCLP family [8]. There have been few studies on shared related mutant genes in NSCLP families.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the etiology of NSCLP is heterogeneous and closely related to genetic and environmental factors [1,3,4,7]. However, a singlegene mutation may contribute more significance in a hereditary NSCLP family [8]. There have been few studies on shared related mutant genes in NSCLP families.…”
Section: Introductionmentioning
confidence: 99%
“…This condition can be divided into syndromic cleft lip with or without cleft palate (SCL/P) and nonsyndromic cleft lip with or without cleft palate (NSCL/P), according to whether it is accompanied by malformations in other organs and systems. NSCL/P patients account for 70% of the total number of patients with CL/P [ 6 ] and are currently an area of interest.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, mild clinical disease was seen in 81% of symptomatic infected individuals, whereas 19% developed severe disease of whom 5% became critically ill 2 . The case fatality rates are 47% in critically ill patients and acute respiratory distress syndrome (ARDS), acute kidney and myocardial injury are the leading causes of death 3 . ARDS is a prominent feature of those who develop severe pneumonia and is thought to occur due to lung injury caused by the production of high levels of inflammatory cytokines 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the cytokine storm directly correlated with the extent of lung injury, multiorgan failure and mortality in patients 5 , 6 . Many different types of inflammatory cytokines such as IL-6, IL-2, IL-7, IL-1β and many others have shown to be associated with clinical disease severity 3 , 5 .…”
Section: Introductionmentioning
confidence: 99%